G212 Paediatric Assessments in Child Protection: How Can We Measure Quality?. (4th June 2013) - Crowley, R; Hyrapetian, M; Day, E; Hodes, D
Abstract : Aims: Child Protection is behind other paediatric specialties in the development of tools to measure the quality of services. We therefore aimed to develop quality indicators in Child Protection that could be used to evaluate paediatric assessments. This study shows how such tools were applied in two Child Protection services and how the resulting outcome data was used to guide service improvement. Methods: A menu of quality measures for paediatric assessment in child protection was formulated from the available guidance and evidence base. Indicators selected by the local team were incorporated into the existing paediatric assessment proforma used for children with suspected maltreatment. The indicators were chosen to be meaningful for the service and to include process as well as outcome measures, without being time-consuming for clinicians. Local teaching sessions informed all doctors about the project and administrators prospectively extracted data for collation in a central database. Results: 84 proformas completed between March and June 2012 were analysed using monthly run charts. Three quality indicators largely within the doctors' control – whether the child was offered a chance to speak to the doctor alone, choose who was present during examination, and attend with a parent or carer – showed some trend towards improvement, which might be expected as a consequence of the 'checklist' function of the proforma. By contrast, the proportion of children whose strategy meeting was attended by a doctor – which requires robust interagency communication in addition to individual action – showed no improvement. Freetext boxes gave qualitative information that has stimulated service improvement, such as ensuring access to a camera to record suspected physical maltreatment. Evidence of ambiguity in one question and suboptimal rates of questionnaire completion have led to modifications in the current cycle of data collection in 2013, the results of which will also be presented and compared. Conclusions: The quality of paediatric assessments can be measured through a clinician-led initiative. We demonstrated that measurement directly stimulates change, particularly when checklists are employed, and can identify specific areas for service improvement. This strategy could be used in other regions and in other areas of child protection.